Life Stress and Health: A Review of Conceptual Issues and Recent Findings - Slavich, George M. (Teaching of psychology, 2016)
Life stress is a central construct in many models of human health and disease. The present article reviews research on stress and health, with a focus on (a) how life stress has been conceptualized and measured over time, (b) recent evidence linking stress and disease, and (c) mechanisms that might underlie these effects. Emerging from this body of work is evidence that stress is involved in the development, maintenance, or exacerbation of several mental and physical health conditions, including asthma, rheumatoid arthritis, anxiety disorders, depression, cardiovascular disease, chronic pain, human immunodeficiency virus/AIDS, stroke, and certain types of cancer. Stress has also been implicated in accelerated biological aging and premature mortality. These effects have been studied most commonly using self-report checklist measures of life stress exposure, although interview-based approaches provide a more comprehensive assessment of individuals’ exposure to stress. Most recently, online systems like the Stress and Adversity Inventory (STRAIN) have been developed for assessing lifetime stress exposure, and such systems may provide important new information to help advance our understanding of how stressors occurring over the life course get embedded in the brain and body to affect lifespan health.